2022
DOI: 10.52547/johe.11.1.48
|View full text |Cite
|
Sign up to set email alerts
|

The Global Prevalence of Anxiety, Depression, and Insomnia among Healthcare Workers during the Covid-19 Pandemic: A Systematic Review and Meta-Analysis

Abstract: Background: Covid-19 disease has posed a serious challenge to countries' healthcare systems at the present outbreak. Meanwhile, the healthcare providers' mental health has been affected. This systematic review and meta-analysis aimed to investigate the pooled prevalence of depression, anxiety, and insomnia among healthcare workers in a short period during the COVID-19 pandemic. Materials and Methods: A systematic search was conducted through Web of Science, Scopus, Medline, and Embase databases, as well as pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 99 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Studies based on COVID-19 have provided emerging evidence of the negative psychological impact on HCWs from different countries [ 12 15 ]. A meta-analysis, which includes 108,931 medical staff individuals from 69 articles across four different countries (China, Iran, Italy and Turkey), reported that the pooled prevalence rates of anxiety, depression, and insomnia were 37%, 34% and 39%, respectively, during the COVID-19 pandemic [ 16 ]. Another meta-analysis by Lee et al [ 17 ], examined a total of 401 studies, involving 458,754 participants from 58 different countries, revealed that the prevalence of depression was 28.5%, anxiety was 28.7%, PTSD was 25.5% and insomnia was 24.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Studies based on COVID-19 have provided emerging evidence of the negative psychological impact on HCWs from different countries [ 12 15 ]. A meta-analysis, which includes 108,931 medical staff individuals from 69 articles across four different countries (China, Iran, Italy and Turkey), reported that the pooled prevalence rates of anxiety, depression, and insomnia were 37%, 34% and 39%, respectively, during the COVID-19 pandemic [ 16 ]. Another meta-analysis by Lee et al [ 17 ], examined a total of 401 studies, involving 458,754 participants from 58 different countries, revealed that the prevalence of depression was 28.5%, anxiety was 28.7%, PTSD was 25.5% and insomnia was 24.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, mental health problems in Healthcare workers during the COVID-19 epidemic have become an urgent public health concern [21]. Numerous review studies have examined the effect of COVID-19 on the mental health of Healthcare workers and showed that mental disorders are highly prevalent among these groups during the pandemic [22][23][24][25]. The Huang et al study showed that the rate of anxiety in medical staff was 23%.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is a reaction to an unknown, internal, ambiguous, and uncontrollable danger among people, especially healthcare workers. Studies indicated a high rate of anxiety among healthcare workers during the COVID-19 pandemic [16]. Furthermore, the nature of this disease increases severe stress-causing reactions such as anger due to changes in working conditions, fear of being a carrier, stigma caused by the disease, anxiety, and insomnia problems in healthcare workers [17,18].…”
Section: Introductionmentioning
confidence: 99%